Novel radar techniques and applications. Volume 1, - Klemm, Richard; Nickel, Ulrich; Gierull, Christoph; Lombardo, Pierfrancesco (Scitech Publishing Inc, 2017)
The following topics are dealt with: real aperture array radar; imaging radar; passive radar; and multistatic radar.
Keywords: Radar.; Imaging systems.; Antenna arrays.; elektronické knihy; electronic books